Update on Peripheral Nerve Electrodes for Closed-Loop Neuroprosthetics - Rijnbeek, Emil H.; Eleveld, Nick; Olthuis, Wouter (Frontiers in Neuroscience, 2018)
In this paper various types of electrodes for stimulation and recording activity of peripheral nerves for the control of neuroprosthetic limbs are reviewed. First, an overview of interface devices for (feedback-)controlled movement of a prosthetic device is given, after which the focus is on peripheral nervous system (PNS) electrodes. Important electrode properties, i.e. longevity and spatial resolution, are defined based upon the usability for neuroprostheses. The cuff electrode, longitudinal intrafascicular electrodes (LIFE), transverse intrafascicular multichannel electrode (TIME), Utah slanted electrode array (USEA), and the regenerative electrode are discussed and assessed on their longevity and spatial resolution. The cuff electrode seems to be a promising electrode for the control of neuroprostheses in the near future, because it shows the best longevity and good spatial resolution and it has been used on human subjects in multiple studies. The other electrodes may be promising in the future, but further research on their longevity and spatial resolution is needed. A more quantitatively uniform study protocol used for all electrodes would allow for a proper comparison of recording and stimulation performance. For example, the discussed electrodes could be compared in a large in vivo study, using one uniform comparison protocol.